Prinsip Kesantunan Berbahasa dalam Interaksi antara Customer service dengan Pelanggan PT KAI - Alvinanda Pentasani; Rusdhianti Wuryaningrum; Anita Widjajanti (Nuances of Indonesian Language, 2021)
The purpose of this study is to describe the principle of politeness in the interaction between customer service and PT KAI's customers clearly naturally. This type of research is descriptive using a qualitative research design. The data in this study are in the form of speech segments and context which are included in the principles of politeness. The research data were collected using observation or observation techniques, listening techniques, and note taking techniques. The results showed that four principles were found, namely the principle of protection, the principle of profit, the principle of discipline, and the method of delivery. Based on the results and discussion, it can be concluded that the principle of politeness in language is clearly realized in customer service interactions with customers of PT KAI.